Design of a Single‐Atom Indiumδ+–N4 Interface for Efficient Electroreduction of CO2 to Formate. Issue 50 (6th October 2020) - Shang, Huishan; Wang, Tao; Pei, Jiajing; Jiang, Zhuoli; Zhou, Danni; Wang, Yu; Li, Haijing; Dong, Juncai; Zhuang, Zhongbin; Chen, Wenxing; Wang, Dingsheng; Zhang, Jiatao; et al.
Abstract: Main‐group element indium (In) is a promising electrocatalyst which triggers CO2 reduction to formate, while the high overpotential and low Faradaic efficiency (FE) hinder its practical application. Herein, we rationally design a new In single‐atom catalyst containing exclusive isolated In δ+ –N4 atomic interface sites for CO2 electroreduction to formate with high efficiency. This catalyst exhibits an extremely large turnover frequency (TOF) up to 12500 h −1 at −0.95 V versus the reversible hydrogen electrode (RHE), with a FE for formate of 96 % and current density of 8.87 mA cm −2 at low potential of −0.65 V versus RHE. Our findings present a feasible strategy for the accurate regulation of main‐group indium catalysts for CO2 reduction at atomic scale. Abstract : A new indium single‐atom catalyst with In δ+ –N4 atomic interface active sites is constructed for electroreduction of CO2 to formate. The system has a more negative potential and high Faradaic efficiency. This approach offers an effective strategy to develop superior main group metal CO2 ER catalysts with not only high activity but also high selectivity.